To find x, you need to isolate/get the variable "x" by itself in the equation:
-1.2(3 - x) = -1.8 Distribute -1.2 into (3 - x)
(-1.2)3 + (-1.2)(-x) = -1.8 (two negative signs cancel each other out and become positive)
-3.6 + 1.2x = -1.8 Add 3.6 on both sides
-3.6 + 3.6 + 1.2x = -1.8 + 3.6
1.2x = 1.8 Divide 1.2 on both sides to get "x" by itself
![(1.2x)/(1.2) =(1.8)/(1.2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/hzogab4polqkxrk0st1tsp7ooq6besxlkn.png)
x = 1.5
PROOF
-1.2(3 - x) = -1.8 Substitute/plug in 1.5 into "x" since x = 1.5
-1.2(3 - 1.5) = -1.8
-1.2(1.5) = -1.8
-1.8 = -1.8